The complicated impact of media use before bed on sleep: Results from a combination of objective EEG sleep measurement and media diaries. (8th February 2022) - Ellithorpe, Morgan E.; Ulusoy, Ezgi; Eden, Allison; Hahn, Lindsay; Yang, Chia‐Lun; Tucker, Robin M.
Abstract: Media use has been linked to sleep disturbance, but the results are inconsistent. This study explores moderating conditions. A media diary study with 58 free‐living adults measured the time spent with media before bed, the location of use, and multitasking. Electroencephalography (EEG) captured bedtime, total sleep time, and the percent of time spent in deep (Stage N3), and rapid eye movement (REM) sleep. Media use in the hour before sleep onset was associated with an earlier bedtime. If the before bed use did not involve multitasking and was conducted in bed, that use was also associated with more total sleep time. Media use duration was positively associated with (later) bedtime and negatively associated with total sleep time. Sleep quality, operationalised as the percent of total sleep time spent in N3 and REM sleep, was unaffected by media use before bed. Bedtime media use might not be as detrimental for sleep as some previous research has shown. Important contextual variables moderate the relationship, such as location, multitasking, and session length.